Cultural and value concepts in oratory - Assel M. , Malikova; Raushan, Imanzhusyp; Sayana K. , Rakimzhanova (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
In today’s period of dynamics and transformation, we can trace the comprehensive search of modern society for the reconstruction of the national cultural and value-based environment. Identifying your own culture from the «Soviet» and «post-Soviet» areas, revision of the spiritual values that came through the years of history, are not limited by the reconstruction of national cultural values of the past. In addition, we should build the cutting-edge ideas and new format values of our culture. Therefore, the current sociocultural situation requires a thorough consideration, a deep understanding of the spiritual and value-based direction, and identifying ways to implement it in a technogenic society (Raev, 2011: 7). We carry out this path through the study of works of scientific thinkers, the speech of our Bi orators, and the national folklore that leads to our cultural value. Kazakh Bi orators are undoubtedly the highest spiritual and cultural value of our people. Thus, Kazakh oratory is one of the universal instruments encompassing the system of identifying cultural values of our people. Its basis is in recognizing the heritage that has been entrusted to us. Cultural values come from the language of the people, mentality, religion, customs, everyday life, folk wisdom, great sayings. Among other things, we believe it is possible to avoid cultural decline, to guide and educate society properly, and to shape today’s axiological system through the relics of oral literature.